MENGANALISA UNJUK KERJA PENGERINGAN IKAN TERI DENGAN SISTEM SIRKULASI UDARA PAKSA - Darmanto, Seno; Setyoko, Bambang (Diponegoro University, 2007)
Experiment is done to know the performance of â€œteri/stolephorusâ€ fish drying with forced air flow system. Theperformance of fish drying is based on moisture of fish, fan/fan velocity, operation temperature and time. Theresearch is done at laboratory by using drying machine with forced air flow system. Based on data analysis itshows that the moisture of fish achieves 20% on fan velocity maximum 2,8 m/s and times operation 3 hours